Awareness, attitudes and participation of teaching staff towards the open content movement in one university - Peter Reed (Association for Learning Technology, 2012)
This research investigates the current awareness of, and participation in, the open content movement at one UK institution for higher education. The open content movement and the open educational resources can be seen as potential methods for reducing time and cost of technology-enhanced learning developments; however, its sustainability and, to some degree, its success are dependent on critical mass and large-scale participation. Teaching staff were invited to respond to a questionnaire. Respondents (n= 59) were open to the idea of sharing their own content and, similar to other studies, demonstrated existing practices of sharing resources locally amongst colleagues; however, there was little formal, large-scale sharing using suitable licenses. The data gathered concurs with other research suggesting a lack of awareness to the Creative Commons licenses as well as a lack of participation in large open educational resource repositories.